ANALISIS PELUANG DAN TANTANGAN PADA PAGUYUBAN CAHAYA TERANG SEBAGAI UKM PENGRAJIN KULIT DI SUKAREGANG GARUT - Ria Satyarini; Muliadi Palesangi (Bina Ekonomi, 2012)
Micro, small and medium enterprise (UMKM) have significant impact to economic development, we can see the increasing Gross Domestic Product (GDP) every year. Government give more concern about the empowerment of UMKM, because most of the UMKM has so much liability especially on managerial aspect. Paguyuban Cahaya Terang (PCT) as an object on this research, is a Paguyuban of craft leather from Sukaregang, Garut. The objective of this research are: (1) to indentify the characteristics of PCT, (2) to identify Strengts, Weaknesses, Opportunities, and Threaths of PCT, (3) make strategi development to increase the capability of PCT. Research methods by observation, Focus Group Discussion (FGD), and interview.Key words: micro, small and medium enterprise (UMKM), analysis SWOT, Strategy development